A global pandemic is not a good time to introduce 'opt-out' for organ donation. (June 2020) - Parsons, Jordan A.; Moorlock, Greg
Following several international examples, England introduced a system of deemed consent for organ donation in May 2020. This had been planned for over a year. However, the unprecedented circumstances of the COVID-19 pandemic raise issues that make the timing of this change unfortunate. The planned public awareness campaign has thus far been overshadowed by media coverage of the pandemic, and will likely continue to be, creating a situation in which a significant portion of the population may be unaware of having become potential organ donors. Further, the immediate impact of the new policy is likely to be significantly weakened by the suspension of the majority of organ donation and transplant activity. In this article, we first outline the details of the new model introduced in England, before considering the impact of the pandemic on transplantation services. We put forward three ethical reasons why, given the unprecedented circumstances, the change should have been postponed. We argue that (1) COVID-19 dominating headlines will prevent widespread awareness of the change, thereby undermining the autonomy of those who do not wish to be donors; (2) a lack of transplant activity during the pandemic will make the impact of the change difficult to measure; and (3) trust in the new system may be damaged given controversial decisions regarding Do Not Attempt Cardiopulmonary Resuscitation orders and the allocation of scarce intensive care resources. These reasons combined make for a shaky start at best and present a risk of the new system failing to achieve its desired and essential effect of increasing the number of voluntary organ donors.